2022
DOI: 10.3390/ijerph19063316
|View full text |Cite
|
Sign up to set email alerts
|

Young People’s Voices and Science for Overcoming Toxic Relationships Represented in Sex Education

Abstract: The scientific literature has presented evidence of how fiction series impact the socialisation of young people’s relationships. However, there is a gap in the evidence on how dialogic interactions overcome the negative impact of the fiction series on the socialisation of toxic relationships. This research analyses dialogic interactions based on scientific evidence related to toxic relationships that contribute to overcoming this type of relationship. First, we developed a communicative content analysis of eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…Eric Kandel [32] stated that simply reading a book can change the anatomy of the brain if we can recall something about the reading afterwards, that is, if we have created a memory. Our results show that the specific scientific evidence read and discussed, which included, among others, the dominant coercive discourse [31], peer group pressure to have disdainful hookups [17], and the characteristics and consequences of disdainful hookups [1], led to Simonetta's recollection of new semantic and emotional details of the episode that were related to what had been read and discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eric Kandel [32] stated that simply reading a book can change the anatomy of the brain if we can recall something about the reading afterwards, that is, if we have created a memory. Our results show that the specific scientific evidence read and discussed, which included, among others, the dominant coercive discourse [31], peer group pressure to have disdainful hookups [17], and the characteristics and consequences of disdainful hookups [1], led to Simonetta's recollection of new semantic and emotional details of the episode that were related to what had been read and discussed.…”
Section: Discussionmentioning
confidence: 99%
“…A month after recall six, in the 11th month of the 7th year, Simonetta read about and was involved in conversations on the coercive dominant discourse [31], which pressures young women to have sporadic sexual-affective relationships with boys who have violent attitudes and behaviors, who humiliate girls. As Simonetta shared in the interview: "I read and commented on scientific literature on coercive discourse".…”
Section: Recall 5: Peer Coercion By Young Women and Enslaving Oneself...mentioning
confidence: 99%
“…The main contribution of this article is the evidence that the women participating affirmed that consent was undermined due to coercive discourse (Racionero-Plaza et al, 2022), which impacted the awakening of sexual relationships. Previous research has demonstrated that coercive discourse is widely prevalent in society; it is publicly displayed in the media (Duque et al, 2022; Rodrigues-Mello et al, 2021; Villarejo-Carballido et al, 2022; Willing, 2022), in schools, and in peer interactions (Torras-Gómez et al, 2019; Valls et al, 2008). These previously developed themes emerged in this research, and we present them here since the interviewees mentioned this pressure in terms of awakening sexual relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Among those discourses, scientific research has found the CDD, which imposes the link between attraction and violence by portraying individuals and relationships with violent attitudes as attractive, fun and exciting R (Gómez, 2015;. Conveyed through different forms of entertainment (movies, shows, music…) and peer interactions, while the CDD presents violent masculinity models as the only attractive and desirable option, egalitarian models are deemed as convenient but lacking attractiveness and excitement (Gómez, 2015;Rodrigues-Mello et al, 2021;Villarejo et al, 2020;Villarejo-Carballido et al, 2022). In this way, the CDD leads to a double-standard frame of mind in which pleasure, fun, excitement and passion are separated from love, care, stability and egalitarianism (Gómez, 2015;Joanpere et al, 2021;Rios-González et al, 2018;Ruiz-Eugenio et al, 2021).…”
Section: State Of the Artmentioning
confidence: 99%